Brief Communication: On the magnitude and frequency of Khurdopin glacier surge events - Quincey, D. J.; Luckman, A. (The Cryosphere, 2014)
The return periods of Karakoram glacier surges are poorly quantified. Here, we present evidence of an historic surge of the Khurdopin Glacier that began in the mid-1970s and peaked in 1979. Measured surface displacements reached >5 km a−1, two orders of magnitude faster than during quiescence. The Khurdopin Glacier next surged in the late 1990s, equating to a return period of 20 years. Surge evolution in the two events shows remarkable similarity suggesting a common trigger. Surge activity in the Karakoram needs to be better understood if accurate mass balance assessments of Hindu-Kush–Karakoram–Himalaya glaciers are to be made.